2018
DOI: 10.1590/abd1806-4841.20185468
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of phototherapy in geriatric patients: a retrospective study

Abstract: BackgroundWhile phototherapy is a well-established treatment for many dermatoses, data from the literature regarding its use in elderly patients are quite limited.ObjectiveIn this study, we aimed to determine the phototherapy indications in geriatric patients and to evaluate the effectiveness and reliability of phototherapy in this group.MethodsThis study included 95 patients of 65 years of age and older who were treated in our phototherapy unit between 2006 and 2015. The data for this study were collected ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 19 publications
5
27
1
Order By: Relevance
“…The median number of sessions was 42 sessions, and the median cumulative dose was 66.8 J/cm 2 . 6 In our study, PASI 75 was achieved by 52.4% patients, with the median number of sessions of 24 and median cumulative dose of 30.1 J/cm 2 . The lower treatment response in our study was likely to be due to a high number of patients that were lost to follow-up, which was 33.3%.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…The median number of sessions was 42 sessions, and the median cumulative dose was 66.8 J/cm 2 . 6 In our study, PASI 75 was achieved by 52.4% patients, with the median number of sessions of 24 and median cumulative dose of 30.1 J/cm 2 . The lower treatment response in our study was likely to be due to a high number of patients that were lost to follow-up, which was 33.3%.…”
Section: Discussionsupporting
confidence: 48%
“…The finding that was quite different in the current study was vitiligo being the second most common indication (26.5%), whereas none of the two aforementioned studies had patients with vitiligo. [6][7] The study by Bulur et al in psoriasis patients revealed that PASI 75 was achieved by 73.7% of patients. The median number of sessions was 42 sessions, and the median cumulative dose was 66.8 J/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sometimes, these patients lack specific skin lesions, and no obvious cause for their chronic (often generalized) pruritus (ie chronic idiopathic pruritus) can be found. Phototherapy can effectively reduce itching in these elderly patients (by up to 80%) and has a minimal risk of acute side effects if the proper UV doses are applied and patients are closely monitored during UV treatment courses . Long‐term side effects, such as the acceleration of skin ageing or higher skin cancer risk, especially in patients with a history of excessive, lifetime sun exposure or who have already received the highest advised cumulative number of UV treatments (around 150‐200 treatments of PUVA or 300 for NB‐UVB), however, have to be considered.…”
Section: Uv Therapy In Other Diseases With Chronic Pruritusmentioning
confidence: 99%